Ultraviolet supercontinuum generation driven by ionic coherence in a strong laser field - Hongbin Lei; Jinping Yao; Jing Zhao; Hongqiang Xie; Fangbo Zhang; He Zhang; Ning Zhang; Guihua Li; Qian Zhang; Xiaowei Wang; Yan Yang; Luqi Yuan; et al. (Nature Communications, 2022)
Supercontinuum generation can be utilized for light source development. Here the authors demonstrate ultraviolet supercontinuum generation from ions due to strong field ionization and multiphoton resonance effect.